Increase in random component of heart rate variability coinciding with developmental and degenerative stages of life. (24th May 2018) - Hayano, Junichiro; Ohashi, Kei; Yoshida, Yutaka; Yuda, Emi; Nakamura, Tooru; Kiyono, Ken; Yamamoto, Yoshiharu
Abstract: Objective : To adapt to a new environment or situation, biological systems explore the most convenient state while moving between attractors by the force of random fluctuation. From this concept, the random component in physiological signals is assumed to increase during developmental and degenerative stages of life. To examine this hypothesis, we measured the age-dependent changes in the random component of heart rate variability (HRV) in 24-h electrocardiography (ECG) big data and in patients with a developmental disorder (DD). Approach : We measured separately regulated and random components of HRV with autoregressive (AR) model fitting, by which the ratio of random component as the fractional variance of AR residual time series. From the ALLSTAR database of about 304 000 ambulatory 24-h ECGs, we randomly extracted the data of 1930 men and 1987 women uniformly for all ages from 0 to 100 years old (100 cases per 5-year strata for each sex). Data were also obtained from male pediatric patients with DD (age 10–15 years). Main results : While the variance of the regulated component of HRV increased from age 0 to 20, decreased with age until 40, and reached a plateau in both sexes, the ratio of the random component was high at birth, decreased with age until 35 in men and 30 in women, and increased again after 75 in men and 85 in women (P  <  0.0001 for all). In patients with a DD, the ratio of the random component was significantly lower than that in age-and-sex matched subjects in the database. Significance : We found that the ratio of the random component of HRV is increased during developmental and degenerative stages of life and that it may be reduced in DD patients during their development.